Residue Removal of Pesticides from Brinjal Using Different Processing Methods - Aasia Akbar Panhwar,; Saghir Ahmed Sheikh,; Aijaz Hussain Soomro,; Ghulam Hussain Abro, (Journal of Basic & Applied Sciences, 2014)
The present study was conducted on the residual removal of six pesticides (bifenthrin, profenofos, endosulfan, imidacloprid difenthiuron and emamectin benzoate) from brinjal by using various house hold processing methods such as washing, detergent washing, peeling, drying and cooking/frying etc. The data revealed that high amount of all pesticide residues (above MRLs) were present and unfit for human consumption in raw form. From water soluble pesticides diafenthiuron reduced more in blanching as compared with imidacloprid and emamectin benzoate. Frying reduced the residues more effectively, rendering it fit for human consumption. Washing followed by frying reduced the fat soluble residues >70% whereas water soluble pesticide residues >80%. It was concluded that each processing was found to be effective in reduction of pesticides residues.